Attitude of Primary Teachers towards In-service Training - CHUTIA, MANUJ KUMAR (THE PRIMARY TEACHER, 2014)
Training is the most essential aspect of teaching profession which develops specific skills about teaching and learning either through pre-service or in-service mode. Only by mere attending of training sessions, efficiency cannot be attained but it requires positive frame of mind towards training. A positive mind set directs teachers to be more attentive to learn different teaching-learning skills which can make them successful in actual classroom situation. This study highlights the inservice training attitude of teachers and finds that in-service training attitude is mostly favourable among primary teachers irrespective of their gender and level of teaching. It also finds significant difference in training attitude between male and female teachers and teachers of lower and upper primary stage of teaching